Temperature regulation and elite young athletes - Falk, B.; Dotan, R. (The Elite young athlete, 2011)
Children and adults employ different thermoregulatory strategies, particularly in dealing with heat stress. Children rely more on `dry` heat exchange, while evaporative heat loss is adults` foremost heat-dissipation venue. Several anatomical, physiological, and psychological factors can affect differential risk of thermal injury in the child vs. the adult athlete, in some situations. Children have greater surface-area- to-mass ratio, lower sweating rate, higher peripheral blood flow in the heat, and a greater extent of vasoconstriction in the cold. They can acclimatise to a similar extent but do so at a lower rate than adults. Differences in perceived exertion and thermal strain, cumulative experience, cognitive development, and decision-making capacity may negatively affect the young athlete`s behaviour under competitive and other situations, possibly subjecting him/her to sub-par performance or to greater risk of thermal injury. However, except for very limited environmental conditions, children in general, and young athletes in particular, are physiologically as capable as adults to handle environmental challenges.